Potret Terkini Objek Wisata Kota Lama Semarang - E. P. Utami; Amin Sujatmiko; Merli Apriyantika (Geography Education, Ivet University, 2020)
The background of this research is to know the state or an overview of the Old City of Semarang, because Semarang Old City tourism object is an important tourist attraction in the city of Semarang especially after undergoing renovations a lot of new, things that can be used as an attraction for tourist. The purpose of this study is (1) To know the history of the Old City of Semarang. (2) To determine a general overview of the Old City of Semarang. (3) To determine the tourist attraction of the Old City of Semarang as a tourist destination. The research is a descriptive qualitative research. Data colletion techniques carried out by observation, interviews, literature study, and documentation that will produce data. Analysis of the data used is Data Reduction, Data Presentation, and Conclusions. The result of this study are (1) The results of this study are (1) The history of the Old City of Semarang begins with the signing of an agreement between the Kingdom of Mataram and the VOC on January 15, 1678. At that time, Amangkurat II handed Semarang to the VOC as payment because the VOC had succeeded in helping Mataram crush the Trunojoyo rebellion. After Semarang was under full VOC power, the city began to be built. (2) The Area of the Old City of Semarang has undergone a revitalization the first phase, and now the second phase is still in process. Thanks to this revitalization of the Semarang Old Town Region can change its bad image, now the Old Town Region of Semarang has become an attractive and exotic tourist attraction in the eyes of tourists. (3) The Area of the Old City of Semarang as a tourist destination certainly has a lot of appeal, namely : Ancient Buildings, Srigunting Park, the Market Klitikan, Bicycle Rental, Facilities complete, Spot the Photo, Café, Restaurant or Culinary, Semarang Creative Gallery, Semarang Contemporary Art Gallery, Old City 3D Trick Art Museum Semarang, and Dream Museum Zone (DMZ). (4) The Old Semarang City Area Management Adminstrator (BPK2LS) has a very important role in the development of the Semarang Old City Area in the past five years. The Government of Semarang City is assisted by the Ministry of PUPR to revitalize since 2017 with the hope that the Semarang Old City Region will become one of the world's cultural heritages from UNESCO (World Heritage) this year.